2023
DOI: 10.1108/jfrc-01-2023-0012
|View full text |Cite
|
Sign up to set email alerts
|

The impacts of corporate governance on firms’ performance: from theories and approaches to empirical findings

Abstract: Purpose This study aims to investigate the relationship between corporate governance (CG) and financial performance in the case of publicly listed companies in Vietnam for the period from 2019 to 2021. The topic is crucial in understanding how effective governance practices can influence the financial outcomes of companies. The study sheds light on the link between CG practice and firm financial performance. It also provides insights for policymakers and practitioners to improve CG practices. Design/methodol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 126 publications
0
11
0
Order By: Relevance
“…Accordingly, OCM systematically overestimate the return on their projects, thus investing excessively in the presence of internal funds (since they are not disciplined by stock markets or constrained by corporate governance mechanisms (e.g. Salehi et al, 2023;Bui and Krajcs ak, 2023). This argument is consistent with Miglo and Brodziak (2019), in the sense that they analysed different scenarios regarding the efficiency of entrepreneurs' decisions.…”
Section: Overconfident Managermentioning
confidence: 67%
See 1 more Smart Citation
“…Accordingly, OCM systematically overestimate the return on their projects, thus investing excessively in the presence of internal funds (since they are not disciplined by stock markets or constrained by corporate governance mechanisms (e.g. Salehi et al, 2023;Bui and Krajcs ak, 2023). This argument is consistent with Miglo and Brodziak (2019), in the sense that they analysed different scenarios regarding the efficiency of entrepreneurs' decisions.…”
Section: Overconfident Managermentioning
confidence: 67%
“…Salehi et al. , 2023; Bui and Krajcsák, 2023). This argument is consistent with Miglo and Brodziak (2019), in the sense that they analysed different scenarios regarding the efficiency of entrepreneurs' decisions.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…This study uses a population of invoice companies listed on the Indonesia Stock Exchange during 2019-2022. The method used in this study to determine the sample is purposive sampling (Djojo, Astuti, and Trisakti, 2023;Ridhwan and Dwiati, 2022;Bui and Krajcsák, 2023).…”
Section: Resultsmentioning
confidence: 99%
“…The available search results provide some insights into the relationship between bookkeeping systems and CG. For example, a study found that good CG practices can positively contribute to a company's financial performance, which makes it crucial for investors to evaluate the quality of CG practices for each listed company so that investment risks can be limited (Bui & Krajcsák, 2023). Another study found that weak CG mechanisms are positively associated with high levels of accounting conservatism, implying that in weak civil law settings, such mechanisms can be used to mitigate agency problems (Nasr & Ntim, 2018).…”
Section: Bookkeeping Systemmentioning
confidence: 99%